Hasil Aman Penurapan Airtanah untuk Kebutuhan Non Pertanian di Kabupaten Bantul - Purnama, Setyawan (Universitas Muhammadiyah Surakarta, 2012)
There are three objectives of this research. First, to calculate the potency of groundwater in Bantul District, second, to calculate the utilization for non agricultural usage and third, to analyze the safe yield of groundwater exploitation for non agricultural usage. To achieve these objectives, groundwater potency is calculated by static method, i.e. by multiplying area width, aquifer thickness and specific yield. Non Agricultural usage is determined by calculating the water utilization for domestic, industry, hotel and livestock. Safe yield is calculated base on area width, groundwater fluctuation and its specific yield. The groundwater resources potency of research area that has area width 506,85 km², amounted 10.059.393.198 m³/year, whereas the safe yield is 260.365.868 m³/year. Water utilization for domestic, industry, hotel and livestock is 21.658.541 m³/year. Reviewed number of potency and utilization, the potency of groundwater in the research area is still able to meet its water needs for non agricultural because the usage have not exceeded its safe yield. Although the groundwater potency is high, the agricultural sector in Bantul District does not use groundwater resources significantly.